Pengembangan Buku Cerita Bergambar Acita Tema Kesehatan Dan Keselamatan Pada Anak Usia 4-5 Tahun - Karin Nugrohowati; Kartika Rinakit Adhe (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Improving and applying health and safety knowledge in early childhood, especially in terms of hand washing during a pandemic is very important to do. Knowledge of washing hands with soap can increase children's awareness of preventing the transmission of Covid-19, as well as assist them in efforts to maintain and improve their health. This research study aims to produce an output in the form of a wordless picture book based on health and safety as a medium for learning to wash hands for children aged 4-5 years. This study uses the Research and Development (R&D) methodology, which is in accordance with the ADDIE development model (Analays, Design, Development, Implementation, Evaluation). Qualitative and quantitative data received through a questionnaire in the form of an assessment questionnaire referring to the Likert scale then assessed using evaluation criteria guidelines to determine the feasibility of ACITA fairy tale books. The study, which involved the Dharma Wanita Kindergarten teacher, Sanan Village, Pakel District, Tulungagung Regency, revealed that the category was quite feasible with a percentage value of 60.6 percent in the feasibility analysis. The assessment of the feasibility of story books conducted by material experts revealed a percentage value of 61 percent and can be classified as quite feasible. Furthermore, the assessment conducted by media experts revealed a percentage value of 65.7 percent and can be classified as quite useful. On the basis of health and safety, it can be determined that the ACITA story book is the right tool to teach hand washing to children aged 4-5 years. washing hands in accordance with the recommendations or procedures for good and correct hand washing, so that children's awareness to maintain and maintain their own health also increases.